People's Republic of China-Hong Kong Special Administrative Region : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
In this study, quantitative, industry-level measures of the intensity of competition are measured. Various methodologies and data used for measuring competition are also discussed. The level of intensity is also compared. The following statistical data are also presented in detail: gross fixed capital formation, selected price indicators, labor force, employment and unemployment, wages, labor productivity, and unit labor costs, property market developments, monetary indicators, equity price developments, revenue, exchange fund balance sheet, loans and advances by type, GDP by sector at current prices, and so on.